Our Experience of Proximally Based Sural Artery Flap with Ilizarov Fixator Around The Knee (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the survival of sural artery flap reconstruction of complex soft tissue defects around the knee and use of ilizarov for fixation of proximal tibial fracture.Methods: This descriptive study was conducted in Orthopedic Department of Sheikh Zayed Medical College/Hospital, Rahim Yar Khan in the period extending from 23rd February 2014 to 23rd June 2019. All the patients fulfilling the inclusion criteria were operated for proximally based sural artery flap to cover the defect and fracture stabilized with Ilizarov fixator. Follow up was for a period of minimum of 06 months for flap survival and up to 1 year for fracture union and knee range of motion.Results: There were total 17 cases including 14(82.3%) male and 3(17.6%) female with mean age 35±9 years. Road traffic accidents were responsible for majority(64.7%,n=11) of cases while 6(35.2%) had gunshot injuries. The flap sizes ranged from 6x6cm up to 12x cm with pedicel length ranges from 4x10cm.Majority(88.2%,n=15) of flap survived. Proximal tibial fractures united in all patients. Full knee range of motion was documented in all the patients at final follow up.Conclusion: Proximally based sural artery fasciocutaneous flap with Ilizarov fixator is a reliable method for reconstruction of complex soft tissue defects around the knee. It has good outcome and only few complications.